A Multi-omics Approach to Unraveling the Microbiome-Mediated Effects of Arabinoxylan Oligosaccharides in Overweight Humans - Alfonso Benítez-Páez (American Society for Microbiology, 2019)
ABSTRACT Long-term consumption of dietary fiber is generally considered beneficial for weight management and metabolic health, but the results of interventions vary greatly depending on the type of dietary fibers involved. This study provides a comprehensive evaluation of the effects of a specific dietary fiber consisting of a wheat-bran extract enriched in arabinoxylan-oligosaccharides (AXOS) in a human intervention trial. An integrated multi-omics analysis has been carried out to evaluate the effects of an intervention trial with an AXOS-enriched diet in overweight individuals with indices of metabolic syndrome. Microbiome analyses were performed by shotgun DNA sequencing in feces; in-depth metabolomics using nuclear magnetic resonance in fecal, urine, and plasma samples; and massive lipid profiling using mass spectrometry in fecal and serum/plasma samples. In addition to their bifidogenic effect, we observed that AXOS boost the proportion of Prevotella species. Metagenome analysis showed increases in the presence of bacterial genes involved in vitamin/cofactor production, glycan metabolism, and neurotransmitter biosynthesis as a result of AXOS intake. Furthermore, lipidomics analysis revealed reductions in plasma ceramide levels. Finally, we observed associations between Prevotella abundance and short-chain fatty acids (SCFAs) and succinate concentration in feces and identified a potential protective role of Eubacterium rectale against metabolic disease given that its abundance was positively associated with plasma phosphatidylcholine levels, thus hypothetically reducing bioavailability of choline for methylamine biosynthesis. The metagenomics, lipidomics, and metabolomics data integration indicates that sustained consumption of AXOS orchestrates a wide variety of changes in the gut microbiome and the host metabolism that collectively would impact on glucose homeostasis. (This study has been registered at ClinicalTrials.gov under identifier NCT02215343.) IMPORTANCE The use of dietary fiber food supplementation as a strategy to reduce the burden of diet-related diseases is a matter of study given its cost-effectiveness and the positive results demonstrated in clinical trials. This multi-omics assessment, on different biological samples of overweight subjects with signs of metabolic syndrome, sheds light on the early and less evident effects of short-term AXOS intake on intestinal microbiota and host metabolism. We observed a deep influence of AXOS on gut microbiota beyond their recognized bifidogenic effect by boosting concomitantly a wide diversity of butyrate producers and Prevotella copri, a microbial species abundant in non-Westernized populations with traditional lifestyle and diets enriched in fresh unprocessed foods. A comprehensive evaluation of hundreds of metabolites unveiled new benefits of the AXOS intake, such as reducing the plasma ceramide levels. Globally, we observed that multiple effects of AXOS consumption seem to converge in reversing the glucose homeostasis impairment.